2014
DOI: 10.1155/2014/120709
|View full text |Cite
|
Sign up to set email alerts
|

Fever of Unknown Origin in a Patient with Confirmed West Nile Virus Meningoencephalitis

Abstract: West Nile Virus (WNV), an RNA arbovirus and member of the Japanese encephalitis virus antigenic complex, causes a wide range of clinical symptoms, from asymptomatic to encephalitis and meningitis. Nearly all human infections of WNV are due to mosquito bites with birds being the primary amplifying hosts. Advanced age is the most important risk factor for neurological disease leading most often to poor prognosis in those afflicted. We report a case of WNV meningoencephalitis in a 93-year-old Caucasian male who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…One published case reports a single PCT level of <0.05 ng/mL in an elderly man with confirmed WNV meningoencephalitis (24). Our case series is the first to report serial PCTs in patients with WNV, and we found that levels remained persistently low.…”
Section: Discussionsupporting
confidence: 60%
“…One published case reports a single PCT level of <0.05 ng/mL in an elderly man with confirmed WNV meningoencephalitis (24). Our case series is the first to report serial PCTs in patients with WNV, and we found that levels remained persistently low.…”
Section: Discussionsupporting
confidence: 60%